Flexible transit routing model considering passengers' willingness to pay. Issue 5 (24th January 2019) - Pei, Mingyang; Lin, Peiqun; Liu, Ronghui; Ma, Yingying
Abstract : This study proposes an alternative flexible transit model with two levels of bus stops, A level and B level. A‐level bus stops are fixed, while B‐level bus stops are flexible and provide service only when passengers indicate a strong willingness to pay (WTP). This fare structure encourages passengers to choose bus stops with their mobile phones or computers. An optimisation model of 0–1 integer‐programming is formulated based on whether certain B‐level stops can be serviced. With a numerical example, the authors compare the performance of the proposed traversing method and a tabu search algorithm, both of which are adapted to solve the model. Finally, a real case is provided to evaluate the proposed transit system against comparable systems (e.g. a fixed‐route transit system and a taxi service), and the result shows that the flexible transit routing model will help both passengers and bus companies, thus creating a win–win situation.